2006
DOI: 10.1523/jneurosci.1342-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Slit Proteins Regulate Distinct Aspects of Retinal Ganglion Cell Axon Guidance within Dorsal and Ventral Retina

Abstract: An early step in the formation of the optic pathway is the directed extension of retinal ganglion cell (RGC) axons into the optic fiber layer (OFL) of the retina in which they project toward the optic disc. Using analysis of knock-out mice and in vitro assays, we found that, in the mammalian retina, Slit1 and Slit2, known chemorepellents for RGC axons, regulate distinct aspects of intraretinal pathfinding in different regions of the retina. In ventral and, to a much lesser extent, dorsal retina, Slits help res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
83
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 59 publications
(85 reference statements)
6
83
0
Order By: Relevance
“…There are multiple factors known to be involved in intraretinal axon pathfinding, including netrin-1, slit, and sonic hedgehog (Deiner et al, 1997;Kolpak et al, 2005;Thompson et al, 2006). These factors comprise an expanding group of molecular cues known to be responsible for the guidance of RGC axons along the optic fiber layer, toward the optic disc and out of the retina.…”
Section: Retinal Expression Of Sema3smentioning
confidence: 99%
“…There are multiple factors known to be involved in intraretinal axon pathfinding, including netrin-1, slit, and sonic hedgehog (Deiner et al, 1997;Kolpak et al, 2005;Thompson et al, 2006). These factors comprise an expanding group of molecular cues known to be responsible for the guidance of RGC axons along the optic fiber layer, toward the optic disc and out of the retina.…”
Section: Retinal Expression Of Sema3smentioning
confidence: 99%
“…The results suggest that Slit1 and Slit2 cooperate to maintain RGC axons in the inner surface of the retina. Strikingly, ectopic RGC axon bundles appear to form preferentially (greater than a 2:1 ratio) in the ventral rather than the dorsal part of the retina [Thompson et al (2006a), their Fig. 3 A, Ϫ/Ϫ and slit1/2 Ϫ/Ϫ organs were intermingled.…”
mentioning
confidence: 92%
“…In 1963, Roger Wolcott Sperry performed his eyeball rotation experiment, still taught to almost every student of neuroscience and developmental biology, which showed that growing axons are guided by chemical factors in their environment. Sperry's (1963) chemoaffinity hypothesis spurred a series of studies to investigate the role of axon guidance molecules in the development of the visual system, including the one that is the focus of a recent article in the Journal of Neuroscience by Thompson et al (2006a). The authors addressed the role of Slit proteins in intraretinal axon guidance, the mechanisms by which axons growing from retinal ganglion cells (RGCs) form a layer at the internal surface of the retina, converging toward the optic disc.…”
mentioning
confidence: 99%
See 2 more Smart Citations